A retrospective evaluation of patients switched from buprenorphine (subutex) to the buprenorphine/naloxone combination (suboxone) - Vorma Helena; Simojoki Kaarlo; Alho Hannu (BMC, 2008)
Abstract Background In Finland, buprenorphine (Subutex) is the most abused opioid. In order to curb this problem, many treatment centres transferred ("forced transfer") their buprenorphine patients to the buprenorphine plus naloxone (Suboxone) combination product in late 2003. Methods Data from a retrospective study involving five different treatment centers, examining the effects of switching patients to Suboxone, were gathered from 64 opioid-dependent patients who had undergone the medication transfer. Results Most patients (90.6%) switched to Suboxone at the same dose of buprenorphine that they had been receiving as Subutex (average 22 mg). The majority of these patients (71.9%) were maintained at the same dose of Suboxone throughout the 4-week study period. During the first 4 weeks, 50% of the patients reported adverse events and at the four month time point, 26.6% reported adverse events. However, due to adverse events one patient only discontinued treatment with Suboxone during the 4-week study period, and five during the four month follow-up period. Of the 26 patients in the follow-up period, Suboxone was misused intravenously once each by 4 patients and twice by 1 patient. These 5 patients all reported that injecting Suboxone was like injecting "nothing" with any euphoria, or that it was a bad experience. Conclusion We conclude that when patients are transferred from high doses (> 22 mg) of buprenorphine to the combination product, dose adjustments may be necessary especially in the later phase of the treatment. We recommend that a transfer from Subutex to Suboxone should be carefully discussed and planned in advance with the patients and after the transfer adverse events should be regularly monitored. With regard of buprenorphine IV abuse, the combination product seems to have a less abuse potential than buprenorphine alone.